Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Solve for "x"
4 (2x (2x - 1) - 1 (2x - 1)) = 0


Sagot :

Answer:

x = 1/2 or 0.5

Step-by-step explanation:

4 • ((2x • (2x - 1)) -  (2x - 1))  = 0

The rule says: To multiply exponential expressions which have the same base, add up their exponents.

In our case, the common base is  (2x-1)  and the exponents are :

         1, as  (2x-1), is the same number as  (2x-1)1

and   1, as  (2x-1)  is the same number as  (2x-1)1

The product is therefore,  (2x-1)(1+1) = (2x-1)2

 4 • (2x - 1)2  = 0

4.2      Solve  :    (2x-1)2 = 0

 (2x-1) 2 represents, in effect, a product of 2 terms which is equal to zero

For the product to be zero, at least one of these terms must be zero. Since all these terms are equal to each other, it actually means:   2x-1  = 0

Add  1  to both sides of the equation :

                     2x = 1

Divide both sides of the equation by 2:

                    x = 1/2 = 0.500

Answer:

x = 1/2.

Step-by-step explanation:

4 (2x (2x - 1) - 1 (2x - 1)) = 0

(2x (2x - 1) - 1 (2x - 1)) = 0

(2x - 1) is common to both parts.

(2x - 1)(2x - 1) = 0

2x - 1 = 0

x = 1/2.